Rehamdil Abdullah - Yasmeen, Mutasim (Feroz sons, Karachi., 2020)
"Rehamdil Abdullah" is a heartwarming story about a kind and compassionate boy. Through various scenarios, the story showcases Abdullah's acts of kindness and generosity. This book aims to inspire young readers to be empathetic, helpful, and considerate towards others.
Keywords: Urdu, Fiction, Short stories